Effect of ascent protocol on acute mountain sickness and success at Muztagh Ata, 7546 m - Bloch, K. E.; Turk, A. J.; Maggiorini, M.; Hess, T.; Merz, T.; Bosch, M. M.; Barthelmes, D.; Hefti, U.; Pichler, J.; Senn, O.; Schoch, O. D. (High Altitude Medicine & Biology, 2009)
Data on acclimatization during expedition-style climbing to >5000 m are scant. We evaluated the hypothesis that minor differences in ascent protocol influence acute mountain sickness (AMS) symptoms and mountaineering success in climbers to Muztagh Ata (7546 m), Western China. We performed a randomized, controlled trial during a high altitude medical research expedition to Muztagh Ata. Thirty-four healthy mountaineers (mean age 45 yr, 7 women) were randomized to follow one of two protocols, ascending within 15 or 19 days to the summit of Muztagh Ata at 7546 m, respectively. The main outcome measures, AMS symptom scores and the number of proceeding climbers, were assessed daily. Mean ± SD AMS-C scores of 16 climbers randomized to slow ascent were 0.06 ± 0.18, 0.26 ± 0.08, 0.41 ± 0.45, 0.53 ± 0.77 at camps I (5533 m), II (6265 m), III (6865 m), and the summit (7546 m), respectively. Corresponding values in 18 climbers randomized to fast ascent were significantly higher: 0.17 ± 0.23, 0.43 ± 0.75, 0.49 ± 0.36, and 0.69 ± 0.54 (p < 0.008, vs. slow ascent in regression analysis accounting for weather-related protocol deviation). Climbers randomized to slow ascent were able to ascend according to the protocol without AMS for significantly more days than climbers randomized to fast ascent (p = 0.04, Kaplan-Meier analysis). More climbers randomized to slow ascent were successful in reaching the highest camp at 6865 m without AMS (odds ratio 9.5; 95% confidence interval 1.02 to 89). In climbers ascending to very high altitudes, differences of a few days in acclimatization have a significant impact on symptom severity, the prevalence of AMS, and mountaineering success.